Taxing profit in a global economy - Devereux, M. P. (Oxford : Oxford University Press, 2021)
The international tax system is in dire need of reform. It allows multinational companies to shift profits to low tax jurisdictions and thus reduce their global effective tax rates. A major international project, launched in 2013, aimed to fix the system, but failed to seriously analyse the fundamental aims and rationales for the taxation of multinationals' profit, and in particular where profit should be taxed. As this project nears its completion, it is becoming increasingly clear that the fundamental structural weaknesses in the system will remain. This book, produced by a group of economists and lawyers, adopts a different approach and starts from first principles in order to generate an international tax system fit for the 21st century.
This edition also issued in print: 2021.
"This is an open access publication, available online and distributed under the terms of a Creative Commons Attribution - Non Commercial - No Derivatives 4.0 International licence (CC BY-NC-ND 4.0)"--Home page.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 10, 2021).
Keywords: International business enterprises -- Taxation; Corporations -- Taxation; Economics; Economics